Pre-Service English Language Teacher Education and the First Years of Teaching: Perspectives from Cyprus. Issue 3 (3rd July 2019) - Kourieos, Stella; Diakou, Maria
ABSTRACT: This study examined the effectiveness of pre-service education in Cyprus, in preparing primary teachers to teach English in primary state schools. A survey and follow up interviews were employed to investigate the following: a) Novice teachers' perceptions of their preparedness to teach English after completing a 4-year Teacher Education program, and b) Challenges encountered during induction years in relation to English language teaching (ELT). Findings point to the inadequacy of pre-service education in Cyprus, in this regard, and call for the reconceptualization of the current practices for preparing primary teachers for the actualities of ELT in state schools.